Pelatihan Penyusunan Gizi Seimbang Bagi Pelatih Pplp Sumatera Barat - Zarwan Zarwan; Edwarsyah Edwarsyah (Jurnal Berkarya Pengabdian Masyarakat, 2019)
Nutritional status is the state of health of an individual or group that is determined by the degree of physical need for energy and other nutrients obtained from food and food whose physical impact is set anthropometrically. A person who has a good nutritional status will grow and develop well and healthy, if a person is healthy he will certainly carry out his daily tasks well, good nutritional status is also an important requirement in achieving optimal health, not only marked by the appearance good but also mental and emotional. High and low nutritional status of a person is determined by the intake of food consumed, good nutritional intake is set according to predetermined standards. A good coach will always pay attention to the athlete's condition from all aspects, one of which is from the nutritional aspect. However, not all trainers understand how to regulate balanced nutrition for athletes. That is why there is a need for balanced nutrition management training for trainers which later is expected to be used for athlete nutrition regulation.